The 203rd Third Meeting of the American Oriental Society - Muhammad Akram (International Institute of Islamic Thought, 1993)
The annual meeting featured panels on the Ancient Near East and Art History; East Asia; Islam, South, and Southeast Asia; The Ancient Near East; and Linguistics. In this report the sessions on Islam are covered. The first day deaJt with Islamic history. Khalid Blankinship (Temple University, Philadelphia, PA) explored "The Background of Sayf ibn 'Umar (d.c. 180/796) and the Nature of His Sources." Sidney H. Griffith (Catholic University of America, Washington, DC) spoke on "Muhammad and the Monk Bahira: Reflections on a Syriac Apologetical Text from Abbasid Times." Tayeb el-Hibri (Columbia University, New York, NY) spoke on "The Regicide of the Caliph al-Amin and the Challenge of Rep resentation in Medieval Islamic Historiography." Christopher Melchert (Wake Forest University, Winston-Salem, NC) explicated the religious ...